An isotopic and genetic study of multi-cultural colonial New Zealand. (April 2021) - King, Charlotte L.; Buckley, Hallie R.; Petchey, Peter; Roberts, Patrick; Zech, Jana; Kinaston, Rebecca; Collins, Catherine; Kardailsky, Olga; Matisoo-Smith, Elizabeth; Nowell, Geoff
Abstract: In the mid-late nineteenth century thousands flocked to the newly-established British colony of New Zealand in the hope of improving their fortunes and forging a better life. While historical records give us an overview of where these people came from, in many cases the individual stories of the people who make up early colonial society have been lost. In this study we use isotopic analysis ( 87 Sr/ 86 Sr, lead isotopes and δ 18 O) and ancient DNA (aDNA) to look at three cemetery populations from early colonial Otago (South Island, New Zealand). One from an organised agricultural settlement, the other two from the Otago goldfields – associated with the early goldrush, and the later influx of Chinese miners to the area. Overall, we assessed individual origins of the people in these cemetery samples, with the aim of better understanding who came to colonial Otago, and how this relates to modern perceptions of Pākehā (non-Māori) identity in New Zealand. Our findings show that many of the individuals presumed to be Chinese from material culture are isotopically distinct, and have Asian derived maternal ancestry, laying the foundation for future work on unidentified historic remains. However, some individuals are associated with seemingly conflicting isotopic and DNA data which hints at the complexity of individual construction of identity in a colonial context. Highlights: This study combines isotopic, genetic and material culture evidence to give new insight into colonial New Zealand identity. Results highlight the multi-cultural nature of goldfields society relative to organised settlements of the period. We note discrepancy between genetic, isotopic and cultural evidence in some individuals, highlighting the complexity of colonial identity.